2016
DOI: 10.1371/journal.pone.0164351
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Fibroblast Growth Factor 21 in Humans with Acute Pancreatitis

Abstract: BackgroundThe metabolic regulator Fibroblast Growth Factor 21 (FGF21) is highly expressed in the acinar pancreas, but its role in pancreatic function is obscure. It appears to play a protective role in acute experimental pancreatitis in mice. The aim of this study was to define an association between FGF21 and the course and resolution of acute pancreatitis in humans.Methods and Principal FindingsTwenty five subjects with acute pancreatitis admitted from May to September 2012 to the Beth Israel Deaconess Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
2
29
1
Order By: Relevance
“…The observed stability of this ratio is consistent with the finding that the intact‐to‐total FGF21 ratio did not change in patients with acute pancreatitis, even though these individuals had significantly higher circulating levels compared with controls . It therefore appears that higher FGF21 levels are associated with higher cleavage of FGF21, thereby maintaining the same intact‐to‐total ratio, although neither of these studies included measurement of FAP levels.…”
Section: Discussionsupporting
confidence: 77%
“…The observed stability of this ratio is consistent with the finding that the intact‐to‐total FGF21 ratio did not change in patients with acute pancreatitis, even though these individuals had significantly higher circulating levels compared with controls . It therefore appears that higher FGF21 levels are associated with higher cleavage of FGF21, thereby maintaining the same intact‐to‐total ratio, although neither of these studies included measurement of FAP levels.…”
Section: Discussionsupporting
confidence: 77%
“…Several cross‐sectional studies have shown that FGF21 levels are increased in obesity and metabolic disease , suggesting the possibility of an FGF21‐resistant state, similar to obesity‐induced insulin and leptin resistance. Elevated FGF21 levels have also been reported in other acute inflammatory states including sepsis and pancreatitis .…”
Section: Introductionmentioning
confidence: 90%
“…Conversely, pharmacologic administration or transgenic overexpression of FGF21 protected the pancreas against ER stress, inflammation and injury in mouse models of pancreatitis (Coate et al, 2017;Johnson et al, 2009Johnson et al, , 2014. In humans, the resolution of acute pancreatitis is correlated with increasing levels of circulating FGF21, further suggesting that FGF21 plays a protective role (Shenoy et al, 2016). These studies suggest a potential pharmacologic role for FGF21 in preventing and treating pancreatitis.…”
Section: Fgf21mentioning
confidence: 80%